Genomic characteristics and prognostic significance of co‐mutated ASXL1/SRSF2 acute myeloid leukemia. Issue 4 (15th February 2021) - Richardson, Daniel R.; Swoboda, David M.; Moore, Dominic T.; Johnson, Steven M.; Chan, Onyee; Galeotti, Jonathan; Esparza, Sonia; Hussaini, Mohammad O.; Van Deventer, Hendrick; Foster, Matthew C.; Coombs, Catherine C.; Montgomery, Nathan D.; et al.
Abstract: The ASXL1 and SRSF2 mutations in AML are frequently found in patients with preexisting myeloid malignancies and are individually associated with poor outcomes. In this multi‐institutional retrospective analysis, we assessed the genetic features and clinical outcomes of 43 patients with ASXL1 mut SRSF2 mut AML and compared outcomes to patients with either ASXL1 (n = 57) or SRSF2 (n = 70) mutations. Twenty‐six (60%) had secondary‐AML (s‐AML). Variant allele fractions suggested that SRSF2 mutations preceded ASXL1 mutational events. Median overall survival (OS) was 7.0 months (95% CI:3.8, 15.3) and was significantly longer in patients with de novo vs s‐AML (15.3 vs 6.4 months, respectively; P = .04 on adjusted analysis). Compared to ASXL1 mut SRSF2 wt and ASXL1 wt SRSF2 mut, co‐mutated patients had a 1.4 and 1.6 times increase in the probability of death, respectively ( P = .049), with a trend towards inferior OS (median OS = 7.0 vs 11.5 vs 10.9 months, respectively; P = .10). Multivariable analysis suggests this difference in OS is attributable to the high proportion of s‐AML patients in the co‐mutated cohort (60% vs 32% and 23%, respectively). Although this study is limited by the retrospective data collection and the relatively small sample size, these data suggest that ASXL1 mut SRSF2 mut AML is a distinct subgroup of AML frequently associated with s‐AML and differs from ASXL1 mut SRSF2 wt / ASXL1 wt SRSF2 mut with respect to etiology and leukemogenesis.